Penerapan logika fuzzy mamdani pada sistem penyiram tanaman stroberi otomatis berbasis mikrokontroler - Siti Olis; Somantri Somantri (Computer Science and Information Technology, 2023)
Technological sophistication in this era is developing so rapidly, technology is increasingly facilitating human work in all fields, including in the agricultural sector, namely in automation systems that can replace human work with machine power, where this system can regulate a job automatically. The problem that often occurs is in the watering system, special plants that have a certain humidity and temperature should be treated regularly with sufficient water content every day, one of which is strawberry plants, from the results of the author's observations that strawberry plants can still grow in 50% humidity - 90% RH and at a temperature of 12 oC - 25 oC, so it should be a concern how strawberry plants can get enough water according to their needs. Of the existing problems, the author provides a solution by creating a microcontroller-based strawberry automatic plant watering system, a system created using the fuzzy mamdani logic method, this logic is used as a system of rules in the duration of watering according to the rules that have been made, this system will display a value notification soil moisture, air temperature and watering time, little, medium, long and dead on the Liquid Crystal Display (LCD).